AMPK regulates Bcl2-L-13-mediated mitophagy induction for cardioprotection - Tomokazu Murakawa; Jumpei Ito; Mara-Camelia Rusu; Manabu Taneike; Shigemiki Omiya; Javier Moncayo-Arlandi; Chiaki Nakanishi; Ryuta Sugihara; Hiroki Nishida; Kentaro Mine; Roland Fleck; Min Zhang; et al. (Cell Reports)
Summary: The accumulation of damaged mitochondria in the heart is associated with heart failure. Mitophagy is an autophagic degradation system that specifically targets damaged mitochondria. We have reported previously that Bcl2-like protein 13 (Bcl2-L-13) mediates mitophagy and mitochondrial fission in mammalian cells. However, the in vivo function of Bcl2-L-13 remains unclear. Here, we demonstrate that Bcl2-L-13-deficient mice and knockin mice, in which the phosphorylation site (Ser272) on Bcl2-L-13 was changed to Ala, showed left ventricular dysfunction in response to pressure overload. Attenuation of mitochondrial fission and mitophagy led to impairment of ATP production in these mouse hearts. In addition, we identified AMPKα2 as the kinase responsible for the phosphorylation of Bcl2-L-13 at Ser272. These results indicate that Bcl2-L-13 and its phosphorylation play an important role in maintaining cardiac function. Furthermore, the amplitude of stress-stimulated mitophagic activity could be modulated by AMPKα2.